Fine ash from the Campanian Ignimbrite super-eruption, ~ 40 ka, southern Italy: implications for dispersal mechanisms and health hazard - Gianchiglia, Flaminia; Ballirano, Paolo; Giaccio, Biagio; Koutsodendris, Andreas; Nomade, Sebastien; Pacella, Alessandro; Palladino, Danilo M.; Pross, Jörg; Veres, Daniel; Sottili, Gianluca (Scientific reports, 2025)
Super-eruptions disperse volcanic ash over vast areas, impacting the environment and human health. Fine ash, particularly its respirable fraction (< 4 µm), poses a significant health hazard by inhalation due to its high dispersal potential. Understanding the aerodynamic properties but also composition of ash particles is fundamental to constrain dispersal and deposition mechanisms in both proximal and distal environments. Current atmospheric dispersal models rely on empirical drag equations calibrated with geometric shape descriptors. However, these models often overlook the effects of the actual particle density, as a uniform componentry is typically assumed. In addition, particles have variable shapes but such data from super-eruptions remains limited and no standardized measurement methods exist. Here, we determine the terminal fall velocity (vt) of fine ash from the Campanian Ignimbrite super-eruption (~ 40 ka, Campi Flegrei), by evaluating the components and particle shapes from proximal to ultra-distal locations. To verify the attribution of the proximal sample to the CI eruption, a 40Ar/39Ar dating was performed, allowing its correlation with the ultra-distal deposits. Results show that, due to the influence of shape and density, glass particles exhibit lower vt compared to mineral phases (vt, feldspar/vt, glass = 1.05 ± 0.03, vt, SiO2/vt, glass = 1.09 ± 0.02), enabling greater travel distances. Drag equations accounting for measured particle shapes differ significantly from spherical approximations. The spherical model overestimation of vt highlights the necessity of shape-specific models to produce more accurate dispersal predictions. Extremely low vt (< 0.1 cm/s) for respirable ash fraction, which indicates prolonged atmospheric suspension and long-time resuspension potential, along with the presence of cristobalite, lead to important implications for health hazards. These findings further enhance our understanding of volcanic ash aerodynamic behaviour and the far-reaching impact of super-eruptions.
Veröffentlicht: 10. Juni 2025
Gesehen am 27.10.2025